Investigation into the Pathology of Idiopathic Systemic Amyloidosis in Four Captive Badgers (Meles meles). (April 2020) - Bianco, C.; Sánchez-Cordón, P.J.; Verin, R.; Godinho, A.; Weyer, U.; Lesellier, S.; Spiropoulos, J.; Floyd, T.; Everest, D.; Núñez, A.
Summary: Systemic idiopathic amyloidosis was described in four captive badgers ( Meles meles ). Two animals (B1 and B2) were not enrolled in any trial, while animals B3 and B4 took part in a vaccine efficacy study and had been challenged with Mycobacterium bovis . A full set of tissues was collected and processed routinely for histopathological, immunohistochemical and ultrastructural studies. Splenomegaly was found in three out of four animals. Histopathological evaluation revealed congophilic, permanganate-resistant systemic amyloid deposits in the tissues of all badgers. Animals B2 and B4 displayed a marked granulomatous response to amyloid within the spleen. Animals B1 and B2 also displayed clinicopathological findings suggestive of chronic kidney disease. Ultrastructural examination identified peculiar star-shaped arrays of amyloid. Immunohistochemical studies were unrewarding. Systemic amyloidosis should be considered among the differentials of wasting in captive badgers.